PLD3 affects axonal spheroids and network defects in Alzheimer’s disease - Yuan, Peng; Zhang, Mengyang; Tong, Lei; Morse, Thomas M.; McDougal, Robert A.; Ding, Hui; Chan, Diane; Cai, Yifei; Grutzendler, Jaime (Nature (London), 2022)
The precise mechanisms that lead to cognitive decline in Alzheimer’s disease are unknown. Here we identify amyloid-plaque-associated axonal spheroids as prominent contributors to neural network dysfunction. Using intravital calcium and voltage imaging, we show that a mouse model of Alzheimer’s disease demonstrates severe disruption in long-range axonal connectivity. This disruption is caused by action-potential conduction blockades due to enlarging spheroids acting as electric current sinks in a size-dependent manner. Spheroid growth was associated with an age-dependent accumulation of large endolysosomal vesicles and was mechanistically linked with Pld3 —a potential Alzheimer’s-disease-associated risk gene 1 that encodes a lysosomal protein 2 , 3 that is highly enriched in axonal spheroids. Neuronal overexpression of Pld3 led to endolysosomal vesicle accumulation and spheroid enlargement, which worsened axonal conduction blockades. By contrast, Pld3 deletion reduced endolysosomal vesicle and spheroid size, leading to improved electrical conduction and neural network function. Thus, targeted modulation of endolysosomal biogenesis in neurons could potentially reverse axonal spheroid-induced neural circuit abnormalities in Alzheimer’s disease, independent of amyloid removal. Amyloid-plaque-associated axonal spheroids are prominent contributors to neural network dysfunction in an Alzheimer’s model and can be reversed by endolysosomal modulation.